Methods of improving technical and functional characteristics of serial budget microprocessor platforms - Lebediev, V. A.; Laktionov, I. S.; Vovna, O. V.; Kabanets, M. M.; Sahaida, P. I.; Dobrovolska, L. O.; Сагайда, П. І. (International Information and Engineering Technology Association (IIETA), 2022)
The relevance of the research is due to the fact that one of the prerequisites for the implementation of Internet of things and Wireless sensor network technologies is the reliable operation of the involved information and measurement systems as parts of the automation and digitalization systems on the rights of subsystems. Thus, the main purpose of the article is to substantiate scientific approaches to increasing the reliability of budget serial microcontroller boards as parts of information and measurement systems by developing methods of improving their technical and functional characteristics. Basic research methods are: methods of critical analysis and logical generalization; methods of computerized monitoring of electrical parameters; methods of experiment planning; methods of computer analysis of measurement results; approaches to experimental testing of information and measuring equipment. The main results of the article are as follows: the current state of scientific research and practical developments on ways to improve the technical and functional characteristics of microprocessor platforms has been analysed; the stabilization characteristics of the output voltage of the microprocessor platform have been investigated; the temperature dependences of the microcontroller at different denominations and types of load have been obtained; the priority areas for further research have been substantiated.
Keywords: Arduino; supply voltage; load current; temperature; stabilizer; microcontroller